2019
DOI: 10.1038/s41396-019-0544-3
|View full text |Cite
|
Sign up to set email alerts
|

The subgingival microbiome associated with periodontitis in type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is a systemic disease, predisposing patients to other inflammatory conditions including periodontitis. The subgingival microbiome, a key player in periodontitis pathogenesis, is not well characterized in T2DM population. To better understand whether the subgingival microbiome is different between T2DM and systemically healthy, nondiabetic (ND) subjects, we performed a longitudinal analysis of the subgingival microbiome in T2DM patients (n = 15) compared with ND subjects (n = 16)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 55 publications
3
86
0
3
Order By: Relevance
“…16 were observed in diabetic patients 16 Furthermore, the shift in composition of the subgingival microbiome from the healthy to the periodontitis state appears to be less prominent in diabetic patients than in normoglycemic individuals, even under similar clinical conditions, with the presence of pathogenic species in the subgingival microbiome being highly correlated between the periodontitis state and the healthy state in diabetic patients. 87 Collectively, these findings indicate that glucose availability may favor the increase in levels of saccharolytic commensals and that this "less traditionally pathogenic" Figure 2C and Figure 3B). 16 Overall, studies utilizing next-generation sequencing revealed reduced microbial diversity in the subgingival microbiome of subjects with diabetes compared with that of healthy controls or nondiabetic subjects with periodontitis, and support the notion that a dysbiotic oral microbiome is a plausible contributory factor in the pathogenesis of diabetes-induced periodontal disease.…”
Section: Diabetesmentioning
confidence: 88%
“…16 were observed in diabetic patients 16 Furthermore, the shift in composition of the subgingival microbiome from the healthy to the periodontitis state appears to be less prominent in diabetic patients than in normoglycemic individuals, even under similar clinical conditions, with the presence of pathogenic species in the subgingival microbiome being highly correlated between the periodontitis state and the healthy state in diabetic patients. 87 Collectively, these findings indicate that glucose availability may favor the increase in levels of saccharolytic commensals and that this "less traditionally pathogenic" Figure 2C and Figure 3B). 16 Overall, studies utilizing next-generation sequencing revealed reduced microbial diversity in the subgingival microbiome of subjects with diabetes compared with that of healthy controls or nondiabetic subjects with periodontitis, and support the notion that a dysbiotic oral microbiome is a plausible contributory factor in the pathogenesis of diabetes-induced periodontal disease.…”
Section: Diabetesmentioning
confidence: 88%
“…More recently, investigators started to use this method to evaluate the effects of different treatment protocols in modulating the oral microbiome. 67,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89] Next-generation sequencing has also enabled rapid expansion of the oral microbial reference genomes available, including uncultured phylotypes. Critical for the study of the oral microbiome was the development of the Human Oral Microbial Database (HOMD, http://www.homd.org).…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Quantitative and qualitative changes in pathogenic periodontal microflora have been observed by various researchers, leading to an oral diabetic dysbiotic state with an increased number of organisms such as Porphyromonas . [ 14 15 16 17 18 ]…”
Section: Q16: Does Diabetes Affect the Periodontal Microbiota And Whementioning
confidence: 99%
“…[ 20 ] Hence, subjects with uncontrolled DM are more prone to a shift toward microbial dysbiosis due to impaired immunity and metabolism. [ 16 ]…”
Section: Q16: Does Diabetes Affect the Periodontal Microbiota And Whementioning
confidence: 99%